RELATIONSHIP BETWEEN ANTIPSYCHOTIC THERAPY WITH CREATININE LEVELS IN SCHIZOPHRENIA PATIENTS - Marisa, Marisa; Endang Suriani; Rinda Lestari; Lisa Fradisa (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2025)
Schizophrenia is a condition of severe mental disorder, characterized by many disturbances in thinking, language, perception and sense of awareness. The use of antipsychotic therapy in the long term can cause damage to kidney function and aggravate the work of the kidneys marked by increased creatinine levels. The purpose of this study was to determine the relationship between duration of antipsychotic therapy and creatinine levels in schizophrenic patients at the Mendawai Health Center. The type of research used is analytic research with a cross sectional approach. In this study the sampling technique used was purposive sampling. This study used the T-Independent Sample T Test. The results showed that there was a relationship between duration of antipsychotic therapy and creatinine levels in schizophrenic patients. It can be seen that the average value of respondents in the category of long antipsychotic therapy is 1.06 and short antipsychotic therapy is 0.71 and the value of equal variance assumed has a sig (2 Talled) p-value of 0.005 (<0.05), so Ha is accepted. So in conclusion there is a significant relationship between the duration of antipsychotic therapy and creatinine levels in schizophrenic patients at the Mendawai Health Center. It is recommended to pay more attention to the side effects of the treatment carried out for further therapy.